Witness about Les Héritiers - Delsaut, Yvette (Tempo Social, 2005)
Les Héritiers, les étudiants et la culture, written by Pierre Bourdieu in partnership with Jean-Claude Passeron and published in Paris in 1964 (Éditions de Minuit), was the result of research done through a questionnaire, based on a sample of students of Letters, in Paris and from a few other French universities. Pierre Bourdieu taught sociology at the University of Lille (North): the statement published herwith tells about the conditions under which the research was undertaken in Lille, under his supervision, and retraces the history of the work, from its elaboration at the European Sociology Centre, to the reception inside and outside university research environment.